Residual Weed Control With Preemergence Herbicides in Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2020)
In this study, herbicides were tested to compare preemergence (PRE) application for weed control in grain herbicides. All herbicides controlled quinoa and crabgrass similarly, as well as Russian thistle late in the season. Halex GT at either rate with atrazine as well as Bicep Lite II Magnum controlled Palmer amaranth less than 90% late in the season. Similarly, these herbicides along with Degree Xtra provided less than 90% kochia control late. Grain yields did not differ between herbicide-treated and non-treated sorghum.
Keywords: chloroacetamide herbicides